Female Performers in British and American Fiction - Straumann, Barbara (Buchreihe der Anglia / Anglia Book Ser., 2018)
The female performer with a public voice constitutes a remarkably vibrant theme in British and American narratives of the long nineteenth century. The tension between fictional female performers and other textual voices can be seen to refigure the cultural debate over the 'voice' of women in aesthetically complex ways. By focusing on singers, actresses, preachers and speakers, this book traces and explores an important tradition of feminine articulation. Drawing on critical approaches in literary studies, gender studies and philosophy, the book conceptualizes voice for the discussion of narrative texts. Examining voice both as a thematic concern and as an aesthetic effect, the individual chapters analyse how the actual articulation by female performers correlates with their cultural visibility and agency. What this study foregrounds is how women characters succeed in making themselves heard even if their voices are silenced in the end.